The Representation of Ecocriticism in the Novel Mata dan Manusia Laut by Okky Madasari - Adelia Savitri; Dwi Wahyuningtyas; Haliza Kanaya Rizky (Nusantara Science and Technology Proceedings, 2022)
This study focuses on the representation of ecocriticism in the children's novel entitled “Mata dan Manusia Laut” by Okky Madasari. Ecocriticism is an approach that explains the relationship between literature and environmental issues. The purpose of this study is to reveal how this novel represents the values for preserving the environment, which the children imitate through the behavior of the Bajo tribe in Wakatobi. By using descriptive qualitative methods and ecocriticism approaches, the results of this study are the values of character education in children that are represented through the mythology of the Bajo tribe such as the belief in the God of the Sea and Queen Octopus as the Guardian of the Sea. This is believed as an effort to preserve the sea. In addition, this novel criticizes human behavior that destroys nature, such as fishing using bombs, polluting the sea with a lot of garbage, and killing living things that protect the marine ecosystem. Thus, besides as the representation of the beauty and natural wealth of Wakatobi, this novel is also an effort to instill the values ??in children that Indonesia's marine wealth with all its potential must be kept in balance.